THE SHIFTING PARADIGM OF ASWAJA AN-NAHDLIYYAH EPISTEMOLOGY IN POSTMODERN ERA - Thohiri, Kholid (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
The Nahdlatul Ulama (NU) are important parts that greatly value the inheritance of the classical Islamic treasures contained in the work of the Imam Mazhab. Its wealth of sources of understanding, NU has its own uniqueway of responding to reform, while maintaining harmony in tradition and cultural heritage, moderate, tolerant, not extreme, as well as promoting goodness and preventing badness. This paper examines the positioning of NU and its relation to Ahlussunnah wa al-Jama?ah (Aswaja) based on the social context that accompanies it and the actors involved in it. There are three locus, places, or cultural fields that have important significance because they are a source of discourse, ideas and practices of mazhab in contemporary NU communities: Pesantren, Islamic College (PTKI) and Non-Governmental Organization (NGO). This paper uses three approaches: Thomas Kuhn?s Shifting Paradigm, Karl Manheim?s Sociology of Knowledge and Abed al-Jabiri?s Epistemology are used to study knowledge that is not only the result of theory, but also part of the process of sociology and epistemology. The results show that the majority of Pesantren when understanding and interpreting Aswaja An-Nahdliyyah are heavier and dominant based on Bayani and Irfani. Whereas the scholar of NU and NGOs that had been Bayani and Irfani shifted to Burhani?s epistemological model. In other words, methodologically they want a change in understanding Aswaja from qauli to manhaji, Bayani-Irfani to Burhani,monolithic-dichotomic to integrative-progressive.